Gestaltic Relationship between K-Pop Idol's Symbol and the Symbols of Their Fans - Adzhan, Zurly Linta; Basharuddin, Zamura; Fitriana, Alviatun Rizqi Eka; Yodawati, Bintang Mahayu; Ramadhani, Nofian Fajar; Kharisma, Nita; Kusuma, Tritan Anugrahayu Jering; Sartika, Yustin (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
Studies on the meaning of the symbols in K-pop Idol’s Logo and the relation with their fandom symbol meaning. Correlation and relationship represented by the meaning of every symbol in a logo from K-Pop Idol and their fandom that bonds each other is beneath the surface. Through this descriptive qualitative study, The analysis aims to unravel the meaning relation based on the phenomenon and how this meaning is carried out. This study employs Reinhart’s Principle of Gestalt Perception to address the description of a form of a perception process by arranging elements with patterns, relationship, and needs into a single unit. This study also employs Gregory’s Boy Bands and Performance of Pop Masculinity to address what branding do the symbols that used by K-Pop Idols and fans try to convey. Calling on the theories to the phenomenon and utilizing Spradleyan analysis, the researchers argue that the K-pop Idol represent their branding based on the symbols meaning in their logo and it is influencing their musical taste for their fans. The relationship and meaning have a continuous relationship and correlation based on the meaning conveyed through the meaning of each symbol from K-Pop idol groups and their fandoms. By using this type of qualitative research with a descriptive approach, it is concluded that the results of the analysis in this discussion can provide in creation of a logo to have a meaning and story that can be conveyed through the meaning in each symbol.